Persepsi Peserta Didik Terhadap Kompetensi Guru Matematika di Tingkat SMA - Wiwik Andriani; Nurmayaningsih Nurmayaningsih (Musamus University, 2023)
The fundamental problem in this study is that there are still teachers who work less than optimally. This can be seen from the existence of teachers who still apply conventional learning, where teachers still apply the lecture method, this is not in line with the demands of the 2013 curriculum where students are required to be more active and creative in learning compared to the teacher. This problem needs to be overcome by knowing students' perceptions of teacher competence. Through student perceptions, a teacher can determine the level of competence he has. By knowing the level of competence that a teacher has, he can increase the competence of students. This research is qualitative research with a descriptive approach, namely describing students' perceptions of the competence of mathematics teachers at the high school level. The focus of this research is students' perceptions of personality competence, pedagogic competence, professional competence, and social competence of mathematics teachers in high school. The subjects of this study were students at SMA Negeri 1 Gowa who were outstanding. The research instrument was the researcher himself because the researcher himself planned what was asked of the research subject in the interview. Data collection techniques were carried out by observation, mastery tests, and interviews conducted with research subjects. This study uses triangulation techniques with data analysis techniques carried out using comparative analysis.